„Ale pachniały zioła…”. Kilka uwag o Orfeuszu i Eurydyce Czesława Miłosza - Jacek, Jacek (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The text is an attempt to prove that the descent to the underworld that the poem depicts (written after Carol’s death) led the Old Poet-Orpheus to absolute, completely objective and maximally interiorized knowledge of loss. The knowledge is of certain weight to the author, who only a few years earlier wrote a dramatic poem entitled ‘It’ (‘To’) and made it the first text of his poetic book under the same title. Unlike the case of the ancient Orpheus, or other later Orpheuses, that knowledge is not, however, the character’s final destination. The ending of the poem allows the reader to assume that — typically of Miłosz — it is an opening to the grand epiphany of existence.